The effect of low-frequency rTMS on auditory hallucinations, EEG source localization and functional connectivity in schizophrenia. (18th January 2023) - Gornerova, Natalie; Brunovsky, Martin; Klirova, Monika; Novak, Tomas; Zaytseva, Yuliya; Koprivova, Jana; Bravermanova, Anna; Horacek, Jiri
Highlights: The clinical effect of low frequency (LF) rTMS in auditory hallucinations was confirmed. LF-rTMS (but not sham) decreased the EEG current densities (sLORETA) in the alpha-2, beta-1, and beta-2 bands in the left fronto-temporo-parietal regions. Active LF-rTMS was followed by a decrease in functional connectivity (eLORETA lagged phase synchronization) in beta oscillations and by a prevailing increase in connectivity in the alpha-2 band. Results suggest that LF-rTMS relieves auditory hallucinations via a suppression or modulation of the local aberrant electrical activity and connectivity. Abstract: Background: Low-frequency repetitive transcranial magnetic stimulation (LF-rTMS) diminishes auditory hallucinations (AHs). The aims of our study were a) to assess the efficacy of LF-rTMS in a randomized, sham-controlled double-blind alignment, b) to identify the electrophysiological changes accompanying the LF-rTMS, and c) to identify the influence of LF-rTMS on brain functional connectivity (FC). Methods: Nineteen schizophrenia patients with antipsychotic-resistant AHs were randomized to either active (n = 10) or sham (n = 9) LF-rTMS administered over the left temporo-parietal region for ten days. The clinical effect was assessed by the Auditory Hallucination Rating Scale (AHRS). The localization of the differences in electrical activity was identified by standardized low resolution brain electromagnetic tomography (sLORETA) and FC was measured by lagged phase synchronization. Results: AHRS scores were significantly improved for patients receiving active rTMS compared to the sham (median reduction: 40 % vs 12 %; p = 0.01). sLORETA revealed a decrease of alpha-2, beta-1, -2 bands in the left hemisphere in the active group. Active rTMS led to a decrease of the lagged phase connectivity in beta bands originating in areas close to the site of stimulation, and to a prevailing increase of alpha-2 FC. No significant differences in current density or FC were observed in the sham group. Limitations: Limitations to our study included the small group sizes, and the disability of LORETA to assess subcortical neuronal activity. Conclusions: LF-rTMS attenuated AHs and induced a decrease of higher frequency bands on the left hemisphere. The FC changes support the assumption that LF-rTMS is linked to the modulation of cortico-cortical coupling.